The age and petrogenesis of alkaline magmatism in the Ampasindava Peninsula and Nosy Be archipelago, northern Madagascar - Cucciniello, C.; Tucker, R.; Jourdan, Fred; Melluso, L.; Morra, V. (Springer-Verlag Wien, 2015)
The Ampasindava alkaline province consists of a series of circular and elliptical intrusions, lava flows, dyke swarms and plugs of Cenozoic age emplaced into the Mesozoic-Cenozoic sedimentary rocks of the Antsiranana basin (NW Madagascar) and above the crystalline basement. The magmatism in the Ampasindava region is linked to a NW-SE trending extensional tectonic setting. New 40Ar/39Ar age determinations on feldspar separate of alkali granites and basaltic dykes yielded ages of 18.01 ± 0.36 Ma and 26 ± 7 Ma, respectively. Alkali basalts and basanites, nepheline syenites and phonolites, and silica saturated-to-oversaturated syenites, trachytes, granites and rhyolites are the main outcropping lithologies. These rocks have sodic affinity. The felsic rocks are dominant, and range from peraluminous to peralkaline. The mantle-normalized incompatible element patterns of the mafic lavas match those of Na-alkaline lavas in within-plate rift settings. The patterns are identical in shape and absolute concentrations to those of the Bobaomby (Cap d’Ambre) and Massif d’Ambre primitive volcanic rocks. These geochemical features are broadly compatible with variable degrees of partial melting of incompatible element-enriched mantle sources. The mineralogical and geochemical variations are consistent with fractional crystallization processes involving removal of olivine, feldspar, clinopyroxene, amphibole, Fe-Ti oxides and apatite. Removal of small amount of titanite explains the concave upward lanthanide pattern in the evolved nepheline syenites and phonolites, which are additionally rich in exotic silicates typical of agpaitic magmas (eudialyte, F-disilicates).